Transparency-by-design: What is the role of open data portals? - Lněnička, Martin; Nikiforova, Anastasija (Elsevier Science BV, 2021)
Transparency in the public sector is one of the most important topics of the current debates on accountable, participatory, and responsive governance. An open government addresses these major topics and aims to encourage the relationships and flows of information between involved stakeholders. This article explores the role of open data portals in supporting these efforts and provides findings regarding the features in the design of these data infrastructures. On the basis of evidence from the concept of transparency-by-design, we argue that transparency is facilitated by open data portals and their features enabling to work with datasets. We therefore propose the list of the categories and corresponding features of open data portals that should constitute the checklist of the portal aiming to achieve the highest level of transparency. The mapping of existing features found in literature to the phases of the transparency cycle demonstrates that open data portals meet the transparency requirements.
Transparency-by-design: Jaká je role open data portálů?
Keywords: transparency; open government data; open data portal; design; features; transparency cycle; transparentnost; open government data; open data portál; design; funkce; cyklus transparentnosti